Identification in models of gasoline pricing - Bachmeier, Lance J. (My University, 2013)
This paper presents evidence that the price of oil does not respond contemporaneously to shocks to the US gasoline market. We find no support for the hypothesis of feedback from the US gasoline market to the price of oil, justifying the identfi cation of impulse response functions by applying a Choleski decomposition (see, e.g., Kilian (2010)). Our results have implications for tests of asymmetric gasoline price responses and forecasting models of the price of crude oil.
Keywords: Gasoline; Crude oil; Error correction; Rockets and feathers; Heteroskedasticity